2013
DOI: 10.1111/gtc.12071
|View full text |Cite
|
Sign up to set email alerts
|

Efficient expression and purification of recombinant human μ‐calpain using an Escherichia coli expression system

Abstract: Calpains comprise a superfamily of Ca 2+ -regulated cysteine proteases that are indispensable for the regulation of various cellular functions. Of these, the mammalian l-and m-calpains are the best characterized isoforms. They are ubiquitously expressed and form heterodimers consisting of a distinct 80-kDa catalytic subunit (CAPN1 for l-calpain and CAPN2 for m-calpain) and a common 30-kDa regulatory subunit (CAPNS1). To date, various expression systems have been developed for producing recombinant calpains for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Cysteine 115 is in the catalytic site of calpain-1, and its mutation in recombinant human calpain-1 completely eliminated calpain-1 activity (Hata et al, 2013), indicating that the C115Y mutation in dog is a calpain-1 null mutation. In humans, we identified three consanguineous families that were homozygous in affected individuals around the CAPN1 region and exome sequencing identified mutations in the CAPN1 gene, and one recessive family with CAPN1 compound heterozygous mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine 115 is in the catalytic site of calpain-1, and its mutation in recombinant human calpain-1 completely eliminated calpain-1 activity (Hata et al, 2013), indicating that the C115Y mutation in dog is a calpain-1 null mutation. In humans, we identified three consanguineous families that were homozygous in affected individuals around the CAPN1 region and exome sequencing identified mutations in the CAPN1 gene, and one recessive family with CAPN1 compound heterozygous mutations.…”
Section: Discussionmentioning
confidence: 99%
“…So what role could SERA5 play? We actually believe it unsurprising that wild-type SERA5 does not exhibit detectable peptidase activity, since experimental replacement with Ser of the nucleophilic Cys in papain, cathepsin L, cathepsin S and the related clan CA enzyme μ-calpain abolishes enzyme activity (Clark and Lowe, 1978 ; Coulombe et al ., 1996 ; Turkenburg et al ., 2002 ; Hata et al ., 2013 ), and numerous examples of active-site Cys-to-Ser mutations of other cysteine proteases including the clan C1B protease bleomycin hydrolase (O’Farrell et al ., 1999 ) and several clan CD caspases (e.g. Van Criekinge et al ., 1996 ) have shown that this mutation invariably results in loss of catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Human cardiac TnT (Merck, 648484-100 μg, purity 95%), recombinant human TnT type 2 (Novus Bio, NBC-1-28765-0.1mg), porcine calpain-1 (porcine erythrocyte, 208712-1mg, Merck Millipore) and domain 1 fragment of CAST (CAST-d1) (TaKaRa Bio) were purchased as purified proteins. Recombinant human calpain-2 and proteolytically inactive mutant calpains, calpain-1:CS (C1:CS) and calpain-2:CS (C2:CS), were produced and purified as described previously [ 20 , 21 ]. Specific activity of calpains was defined by casein assay (100–350 U/mg) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%